Interoceptive awareness and emotion regulation through a theatre-based relational health intervention: a heart rate variability study - Levin, Ruth (Department of Psychiatry and Mental Health, 2025)
Relational health is considered a key indicator of mental health and requires interoceptive awareness and emotion regulation. The ability to attune to and regulate one's thoughts and emotions for well-being is the precursor to healthy relationships that are empathic, compassionate, and authentic. Within the field of contemplative science, mindfulness-based interventions enhance relational health by targeting self-awareness of entrenched reactivity and behaviour and the regulation thereof to improve relational health. Similarly, theatre pedagogy, an embodied and relational training, targets mindfulness of the relationship between one's internal milieu and external behaviour. The aim of this study was to test whether a new intervention, the Theatre-Based Relational Health intervention, over six weeks, effects changes pre to post intervention in interoceptive awareness and emotion regulation in stressful relationships to improve relational health. This study hypothesised that entraining interoceptive awareness with an emotion regulation exercise, the Golden Nugget Listening Breathing Exercise, in the context of stressful relationships, will improve relational health. Two studies were conducted. A pilot study assessed the feasibility and acceptability of the intervention and measured the preliminary effectiveness using behavioural questionnaires and qualitative interviews. A main study followed using an additional neurobiological measure, heart rate variability, in a waitlist-control design. A third group engaged as a retest group, received the breathing-only intervention. Heart rate variability measures with questionnaires were used to determine associations that index interoceptive awareness in the brain-heart nexus. Heart rate variability measures were used to index cardiac autonomic outflow during emotion regulation. The Multidimensional Assessment of Interoceptive Awareness Scale and the Five Facet Mindfulness Scale were used to index interoceptive awareness, and in conjunction with the Self-Compassion Scale, were used to measure emotion regulation. Qualitative interviews were conducted post intervention to explore how participants experienced the Theatre-Based Relational Health intervention and changes pre to post in their relational health. Novel results were found with associations between increased heart rate variability measures and improvements in subscales ‘Not-Worrying' and ‘Trusting' of the Multidimensional Assessment of Interoceptive Awareness Questionnaire and improvements in the subscales ‘Observe' and ‘Acting with Awareness' of the Five Facet Mindfulness Scale. Corroborative results verified associations between increases in heart rate variability and improvement in the subscale ‘Over-Identification' and the ‘Total Score' of the Self-Compassion Scale. Behavioural results showed significant increases in interoceptive awareness through the regulation subscales of the Multidimensional Assessment of Interoceptive Awareness and the Five Facet Mindfulness Scale, and emotion regulation through increases in the combination of all three scales. In the qualitative interviews, participants shared their experiences of substantial improvements in their relational health post-intervention. They described developing self-awareness amidst triggers, self-acceptance, self-care, and managing conflict using the Golden Nugget Listening Breathing Exercise and cited the group as a support system. The results in this study suggest that adapted character development exercises from theatre pedagogy might serve as a socio-cognitive and somatosensory tool for the development of interoceptive awareness. Overall, the intervention showed promise in improving relational health, and the Golden Nugget Listening Breathing Exercise may develop emotion regulation in the context of stressful relationships.